Genderlect Investigation In Susan Glaspell's A Jury of Her Peers - Meryem Ayan (European Scientific Journal, ESJ, 2016)
The development of stylistic analysis that focuses on the role of the linguistic codes of the text dates back to the classical period. From the classical period onwards there has been continued interest among scholars in the relation between patterns of language (linguistic descriptions) and the meaning (interpretation) in the text. Feminist stylistics, a sub-discipline of stylistic analysis, is the study and interpretation of a text from a genderized and feminist linguistic perspective. Feminist stylistics, providing an insight into aspects of feminist writing and stylistics focus on the analysis of the factors which determine the meaning of text in its social context. Feminist stylisticians highlight in a systematic manner the self conscious attempts by female writers to modify traditional modes of language use from a female perspective. For years women’s' writing and language were criticized of not being stylistically unique but recent feministic researches have shown that women’s' writings were ‘ecriture feminine’ and language was stylistically unique, therefore modern feminists indicate that there is difference between male and female writing and language use. This paper, aims to focus on feminist stylistics by exemplifying the difference between male and female language use that is referred as genderlect in Susan Glaspell’s short story A Jury of Her Peers.